Impact of a Higher (Dairy) Protein Weight Loss Intervention on Function and Body Composition in Obese Older Adults with Limited Functional Performance. (29th May 2020) - Starr, Kathryn Porter; Rincker, Jamie; Vliet, Stephan van; Patel, Dipa; McDonald, Shelley; Pieper, Carl; Bales, Connie
Abstract: Objectives: The combination of obesity with age-related loss of muscle mass and strength creates a cumulative risk to function and the physical ability of older adults to sustain daily activities. The aim was to determine whether a higher protein intake can improve function and protect lean mass in older adults following a diet and exercise obesity intervention. Methods: Obese (BMI ≥30 kg/m 2 ) older (≥60 yrs) participants (female n  = 50; male n  = 15; 46% black) with functional limitations (Short Physical Performance Battery (SPPB) score = 9.1 ± 1.4 out of 12) were randomized to an RDA-level protein weight loss regimen (0.8 g/kg bw/d; Control; n  = 33) or a higher protein arm (1.2 g/kg bw/d, with ≥30 g high quality protein (predominantly dairy) at each meal; Protein; n  = 32). Both groups followed a hypo-caloric diet and participated in 2 supervised low-intensity chair exercise sessions per wk and 1 session/wk at home. Measurements at baseline, 3 and 6 months included body weight, SPPB, 6-minute walk time, 8-foot up and go test, and body composition (BODPOD). Results: Mean baseline characteristics were BMI 35.0 ± 4.9 kg/m 2 and age = 69.5 ± 6.2 yrs. At 6 months, weight loss and body fat reduction were significant ( P <   0.001) in both Control (7.0% weight) and Protein (6.6% weight) with no group difference. The slight (<−1 kg) change in lean mass was not different between groups. At 3 and 6 months, SPPB scores significantly increased in both groups ( P <   0.01) with no difference between groups. However, at 3 months, the Protein group had significantly greater improvements in distance walked in 6 minutes (Protein = 48.3 ± 71.7 m; Control = 3.4 ± 69.3 m; P  = 0.01) and timed 8-foot up and go (Protein = −0.9 ± 1.0 s; Control = −0.3 ± 1.2 s; P  = 0.04) compared to control; no difference between groups for either test at 6 months. Conclusions: We found that a hypocaloric balanced, higher protein diet (predominantly low-fat dairy) improved distance walked in 6 minutes and 8-foot up and go times at the 3 month time point; this group difference was absent at 6 months, when the improvements in these tests, as well as SPPB were equal between groups. Further study is needed to assess the potential that higher protein intake accelerates function responses to a diet plus exercise intervention for obese older adults. Funding Sources: The National Dairy Council and US Department of Veterans Affairs Rehabilitation Research and Development Program.